Image_1_Case Report: Ambergris coprolite and septicemia in a male sperm whale stranded in La Palma (Canary Islands).JPEG - Antonio Fernández; Cristian Suárez-Santana; Paula Alonso-Almorox; Francesco Achille Consoli; Zuleima Suárez González; Ignacio Molpeceres-Diego; Claudia Iglesias González; Marta Lorente Hernández; Amaranta Hugo Pérez; José Luis Martín-Barrasa; Laura Iglesias Llorente; Félix M. Medina; et al. (2024)
On the 21st of May 2023, a dead adult male sperm whale (Physeter macrocephalus) of 13 m in length and estimated weight of around 18,000 kg was reportedly stranded at Playa Los Nogales, La Palma, Canary Islands, Spain. A necropsy was performed 48hpm. A 50 cm diameter and 9.5 kg coprolite was found obstructing the caudal colon-rectal lumen. Necro-hemorrhagic lesions were found in heart muscles and three different bacteria of intestinal origin were isolated and identified (Edwarsiella tarda, Hathewaya limosa and Clostridium perfringens). It is reported a lethal septicemia of intestinal origin associated with ambergris coprolite as cause of death in this sperm whale.